Type I Interferon at the Interface of Antiviral Immunity and Immune Regulation: The Curious Case of HIV-1 - Adriano Boasso (Scientifica)
Type I interferon (IFN-I) play a critical role in the innate immune response against viral infections. They actively participate in antiviral immunity by inducing molecular mechanisms of viral restriction and by limiting the spread of the infection, but they also orchestrate the initial phases of the adaptive immune response and influence the quality of T cell immunity. During infection with the human immunodeficiency virus type 1 (HIV-1), the production of and response to IFN-I may be severely altered by the lymphotropic nature of the virus. In this review I consider the different aspects of virus sensing, IFN-I production, signalling, and effects on target cells, with a particular focus on the alterations observed following HIV-1 infection.